The natural course of carpal tunnel syndrome in a working population - Barbara A Silverstein; Z Joyce Fan; Dave K Bonauto; Stephen Bao; Caroline K Smith; Ninica Howard; Eira Viikari-Juntura (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVE: The aim of this study was to assess prevalence, incidence, and persistence of carpal tunnel syndrome (CTS) and associated symptoms over a one-year period in a working population. METHODS: We conducted a one-year prospective study of 418 active workers in 12 worksites. Detailed health interviews, psychosocial questionnaires, and electrophysiological studies [ie, nerve conduction velocity (NCV) tests] were conducted at baseline and one-year follow-up. Individual-observed exposure assessments of wrist posture, hand activity, and hand forces were conducted. RESULTS: Prevalence of CTS cases at baseline was 10.8% [95% confidence interval (95% CI) 7.8-13.7%] on the dominant side and 6.0% (95% CI 3.7-87.3%) on the non-dominant side; CTS symptoms were 14.1% (95% CI 10.8-17.5%) and 11.0% (95% CI 8.0-14.0%), respectively. Incidence of CTS cases were 7.5% (95% CI 4.8-10.2%) and 5.6% (95% CI 3.3-7.9%), respectively. Higher proportions of subjects with current symptoms or positive electrophysiological test findings at baseline became CTS cases at one year compared to those with neither (28.6% and 13.9%, respectively, versus 0.5%). One-year persistence of CTS case status was 44.4% (95% CI 29.9-59.0%) for the dominant hand and 52.0% (95% CI 32.4-71.6) for non-dominant hand. There were significant differences at baseline between asymptomatic subjects and CTS cases with respect to higher job demands (P=0.027), lower job satisfaction (P=0.036), lower general health (P=0.0009), higher exposure to vibrating hand tool use (P=0.039), and greater time using a forceful power grip (P=0.035) among cases. CONCLUSIONS: CTS symptoms more than positive NCV test results alone appear to predict CTS at one year. Persistence of CTS at one year is high.